EpCAM expression in primary tumour tissues and metastases: an immunohistochemical analysis. Issue 5 (17th March 2011) - Spizzo, Gilbert; Fong, Dominic; Wurm, Martin; Ensinger, Christian; Obrist, Peter; Hofer, Carina; Mazzoleni, Guido; Gastl, Guenther; Went, Philip
Abstract : Aims: Epithelial cell adhesion molecule (EpCAM) is a cell surface protein with oncogenic features that is expressed on healthy human epithelia and corresponding malignant tumours. EpCAM expression frequently correlates with more aggressive tumour behaviour and new EpCAM-specific therapeutic agents have recently been approved for clinical use in patients with cancer. However, no consensus exists on how and when to evaluate EpCAM expression in patients with cancer. Material and methods: EpCAM expression was assessed by a well-established immunohistochemical staining protocol in 2291 primary tumour tissues and in 108 metastases using the EpCAM-specific antibody clone VU1D9. A total immunostaining score was calculated as the product of a proportion score and an intensity score. Four expression subgroups (no, weak, moderate and intense) were defined. As described previously, the term 'EpCAM overexpression' was reserved for tissues showing a total immunostaining score >4. Results: EpCAM was highly expressed in most tumours of gastrointestinal origin and in some carcinomas of the genitourinary tract. However, hepatocellular carcinomas, clear cell renal cell cancer, urothelial cancer and squamous cell cancers were frequently EpCAM negative. EpCAM expression in breast cancer depended on the histological subtype; lobular histology usually showed no or weak expression. Most metastases were EpCAM positive and they frequently reflected the expression phenotype of the primary tumour. Conclusion: EpCAM expression was detected on adenocarcinomas of various primary sites. If EpCAM-specific antibodies are intended to be used in patients with cancer, we recommend prior immunohistochemical evaluation of EpCAM expression, particularly in patients with renal cell cancer, hepatocellular carcinoma, urothelial carcinoma, breast cancer and squamous cell carcinomas.